CHARACTERISTICS OF LEVELS OF FORMATION SELF-CONTROL OF STUDENTS (Pedagogy of Higher and Secondary Education, 2004)
In the article, the description of levels of formed abilities and skills of self-control of pupils in the process of their educational-cognitive activity is considered.